Estimativa dos fluxos de energia superficiais utilizando o modelo de superfície noah modificado para culturas alagadas - Timm, Andréa Ucker (2011)
The following study quantifies the seasonal and annual distribution of energy balance components (sensible heat fluxes, latent, soil, and net radiation) in this flooded irrigated rice ecosystem in Southern Brazil for three different periods (Fallow 1: 22 July 2003 to 24 November 2003; Rice: 25 November 2003 to 04 April 2004 and Fallow 2: 05 April 2004 to 21 July 2004). In addition, it has been applied the Noah Land Surface Model with the objective of estimating the surface energy fluxes. An important challenge is to implement a new version of Noah Land Surface Model applied to flooded agricultural land called Noah-Paddy. The stabilization of the models has been performed using the atmospheric forcing data obtained from South American Land Data Assimilation System (SALDAS) for the period 22 July 2000 to 21 July 2003. The models were simulated using the observed atmospheric forcing from a micrometeorological tower installed on a flooded irrigated rice paddies located in the city of Paraíso do Sul - RS. The initial conditions were obtained from the last time step of the spin-up experiment performed with atmospheric forcing data of SALDAS. The models results were compared with experimental data for surface energy fluxes. From the simulated results generated by the Noah Land Surface Model, it seems that when the rice crop is flooded, the model does not satisfactorily represents the experimental data. However, using the Noah-Paddy model the components of surface energy balance are more realistic for the system surface-water-atmosphere. The most important contribution performed in this research was to describe the diffent physical processes originated by the presence of a body of water between the soil surface and the atmosphere. This physical system occorr always in flooded agricultural crops in wich the rice paddies field are predominant.